The Novel KIF1A Missense Variant (R169T) Strongly Reduces Microtubule Stimulated ATPase Activity and Is Associated With NESCAV Syndrome - Aguilera, Cinthia; Hümmer, Stefan; Masanas, Marc; Gabau, Elisabeth; Guitart, Miriam; Jeyaprakash, A. Arockia; Segura, Miguel F.; Santamaria, Anna; Ruiz, Anna (Frontiers in Neuroscience, 2021)
KIF1A is a microtubule-dependent motor protein responsible for fast anterograde transport of synaptic vesicle precursors in neurons. Pathogenic variants in KIF1A have been associated with a wide spectrum of neurological disorders. Here, we report a patient presenting a severe neurodevelopmental disorder carrying a novel de novo missense variant p.Arg169Thr (R169T) in the KIF1A motor domain. The clinical features present in our patient match with those reported for NESCAV syndrome including severe developmental delay, spastic paraparesis, motor sensory neuropathy, bilateral optic nerve atrophy, progressive cerebellar atrophy, epilepsy, ataxia and hypotonia. Here, we demonstrate that the microtubule stimulated ATPase activity of the KIF1A is strongly reduced in the motor domain of R169T variant. Supporting this, in silico structural modeling suggests that this variant impairs the interaction of KIF1A motor domain with microtubules. The characterisation of the molecular effect of the R169T variant on the KIF1A protein together with the presence of the typical clinical features indicates its causal pathogenic effect.